KOMITMEN KEPEMIMPINAN PADA VISI MISI PENDIDIKAN ISLAM - Fara Fariha Rodliyana; Samas Muizul Mala (As-Sulthan Journal of Education, 2026)
Leadership plays a strategic role in determining the success of Islamic educational institutions, particularly in realizing the established vision and mission. A recurring problem is that the vision and mission are not consistently implemented in institutional policies and practices, which ultimately affects educational quality. This study focuses on examining leadership commitment to the vision and mission of Islamic education, including the concept of leadership, the nature of vision and mission, forms of leadership commitment, and their implementation in managing Islamic educational institutions. The research employs a qualitative approach using library research, analyzing relevant literature through descriptive-analytical methods involving data condensation, data display, and conclusion drawing. The findings indicate that strong leadership commitment to the vision and mission significantly contributes to improvements in academic and non-academic quality, the strengthening of students’ character, enhanced performance of teachers and educational staff, as well as the sustainability and competitiveness of Islamic educational institutions. Leadership commitment manifested through policy consistency, exemplary conduct, and the development of an Islamic organizational culture is a key factor in realizing quality, character-based, and sustainable Islamic education.